EVALUATION OF THE EMPOWERMENT PROGRAM FOR WOMEN HEADED OF FAMILIES IN THE FAMILY PLANNING POPULATION CONTROL AGENCY. AND WOMEN'S EMPOWERMENT, CHILD PROTECTION (DP2KBP3A) SUKABUMI CITY - Pebriyanti, Neng Reni; Purwanti, Dian; Nur, Tuah (DIA: Jurnal Administrasi Publik, 2024)
This research aims to evaluate the effectiveness of the Women-Headed Family Empowerment Program implemented by the Population Control Service, Family Planning and Women's Empowerment, Child Protection (DP2KBP3A). This research uses an evaluation approach based on the Stufflebeam model, which includes context, input, process and product as the main dimensions of evaluation. The research method used is qualitative. Data was collected through surveys, interviews and documentation studies to gain a holistic understanding of program implementation. The research results show that the Female Head of Family Empowerment Program has had a positive impact on participants. There has been a significant increase in the skills and knowledge of female heads of families in managing economic resources and overcoming the challenges of daily life. In addition, this program has succeeded in increasing access of female heads of families to reproductive health services and education